Sinergi Pemerintah Desa Dan Sektor Swasta Dalam Pengembangan Program Csr Berbasis Ekonomi Berkelanjutan Di Kabupaten Kutai Timur - Reni Alfionita Mustafa; Muh. Jamal; Muhammad Hairul Saleh (Bajang Institute, 2026)
The implementation of Corporate Social Responsibility (CSR) in areas characterized by industrial activities and natural resource extraction is not only related to corporate social responsibility but is also an integral part of regional development governance. East Kutai Regency has a strong economic structure based on mining, plantations, and industrial activities, making private-sector involvement strategically important in supporting community development, particularly in rural areas. This study aims to analyze the synergy between village governments and the private sector in developing sustainable economy-based CSR programs in East Kutai Regency. The study employs a qualitative approach with a case study design and a collaborative governance perspective. Data were obtained through the analysis of regulations, local government documents, CSR program documents, and relevant scientific literature. The analysis focuses on program alignment, role distribution, coordination, community participation, economic empowerment, and program sustainability. The findings indicate that East Kutai Regency has relatively substantial CSR resources. In one village development program document, CSR realization from several companies was recorded at approximately IDR 68.35 billion. At the implementation level, there are practices of synergy between corporate and village government resources, including village facility development, community enterprise development, and economic empowerment programs. For example, the Prolekta Program of PT Pertamina EP Sangatta generated five new business subunits through the development of stingless-bee farming and educational tourism, while the MSME mentoring program of PT Indexim Coalindo helped supported products enter markets in Belgium and Singapore. These findings indicate that CSR has the potential to evolve from social assistance toward productive economic empowerment. However, the scale of resources and number of programs do not automatically guarantee sustainability. Challenges remain in program synchronization, community capacity, mentoring, communication, and the risk of dependence on companies. This study emphasizes that village governments should be positioned as actors that identify community needs and participate in joint planning, while companies should act as development partners that provide resources and expertise. Thus, the success of CSR is determined not by the amount of funding distributed, but by the ability of government, companies, and communities to synergize in transforming these resources into sustainable economic capacity.